Financial Inclusion and Income Inequality in Sub-Saharan Africa: The Role Play by Mobile Money (Global Journal of Management and Business Research, 2020)
The objective of this work is to determine whether the effect of mobile money on financial inclusion allows the latter to significantly reduce income inequalities in Sub-Saharan Africa. The work of Seshamani and Tounkara (2018) suggests that financial inclusion is not yet working in this direction and that mobile can remedy it. In order to achieve this objective, thanks to data from FAS, SWIID, WDI (2019) and WGI (2019), the PCSE, generalized least squares and instrumental variables are applied on a sample of 04 countries between 2010 and 2014.
Keywords: financial inclusion; income inequality; mobile money